Royal Canadian Academy of Arts : 88e Exposition Annuelle. - The Montréal Museum of Fine Arts, Montréal; The Saskatoon Gallery and Conservatory Corporation, Saskatoon; The Art Gallery of Greater Victoria (Toronto : Royal Canadian Academy of Arts, 1967)
Beament, Tib ; Caiserman-Roth, Ghitta ; Collier, Alan C. ; Comfort, Charles ; Deutsch, Peter ; Erickson, Arthur ; Jarvis, Donald ; Landsley, Patrick ; Lemieux, Jean-Paul ; Lorcini, Gino ; Menses, Jan ; Richards, Cecil ; Schmidt, Marianna ; Smith, Gordon A. ; Tolgesy, Victor ; Tondino, Gentile ; Wilson, York
Engels & Frans
88th Annual Exhibition 1967, The Montréal Museum of Fine Arts, Montréal, October 27 - November 22, 1967 ; The Saskatoon Gallery and Conservatory Corporation, January 1 - January 31, 1968 ; The Art Gallery of Greater Victoria, February 27 - March 18, 1968
boek